REAKSI RADANG - Ratna Farida (Faculty of Dentistry, Universitas Indonesia, 2015)
Inflammatory respone is a non-specific response to an injurious stimulus in vascularized tissue. The purpose of this response is to destruct noxious agent, limitation of its spread, and preparation for reconstitution or repair of injured area. Inglammation is classified into acute and chronic types. The classical features of redness, swelling, warmth, pain and loss of function, all of which reflect the effects of cytokines and other inflammatory mediators on the local blood vessels in acute inflammation. The cellular response is mainly of neutrophil polymorphonuclear leukocytes. Furthermore, chronic mononuclear cells-macrophages, lymphocytes, and plasma cells. A proliferation of blood vessels also occurs. There is also associated collagen production by fibroblasts resulting fibrosis. Cytokines secreted by macrophages play prominent roles in inflammation. However, other soluble factors, such as vasoactive amines, lipid mediators, complement fragments C5a, C3a, and C4a, prostacyclin and nitric oxide are also major players in inflammation. The inflammatory reactions in the mouth and teeth are identical to inflammatory reactions anywhere else in the body. Such as pulpitis is similar to inflammation in other connective tissue anywhere in the body.